1972
DOI: 10.2134/agronj1972.00021962006400050045x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Furrow Opener, Corn Plant Spacing, and Yield1

Abstract: In spite of proven yield advantages for corn (Zea mays L.) planted in narrow rows or at equidistant spacings, equipment expense and weed control disadvantages have slowed acceptance of these cultural practices. Improving plant spacing uniformity by decreasing the intra‐row spacing variance should be as effective in increasing yields as improving spacing uniformity by decreasing row width. To aid in determining what investment may economically be made to improve intra‐row plant spacing uniformity, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…Important yield decreases in response to uneven seedling emergence were also observed by Nafziger et al (1991) and Liu et al (2004a) Uneven plant spacing tended to result in lower maize yields. Negative effects of unevenness in plant spacing on maize yield were observed by Krall et al (1977) and Vanderlip et al (1988) in contrast to results reported by Erbach et al (1972), Muldoon and Daynard (1981), and Liu et al (2004b) In soybean, yield did not respond to increases in within‐row plant spacing variation nor in seedling emergence variation as it was reported by Egli (1993a) In agreement with these findings, estimations based on Eq. [4] indicated that increases in CV for Vp did not affect soybean yield but reduced maize yield (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Important yield decreases in response to uneven seedling emergence were also observed by Nafziger et al (1991) and Liu et al (2004a) Uneven plant spacing tended to result in lower maize yields. Negative effects of unevenness in plant spacing on maize yield were observed by Krall et al (1977) and Vanderlip et al (1988) in contrast to results reported by Erbach et al (1972), Muldoon and Daynard (1981), and Liu et al (2004b) In soybean, yield did not respond to increases in within‐row plant spacing variation nor in seedling emergence variation as it was reported by Egli (1993a) In agreement with these findings, estimations based on Eq. [4] indicated that increases in CV for Vp did not affect soybean yield but reduced maize yield (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…These genotypic effects would be some of the reasons for the contrasting responses of maize crops to variability in intrarow spacing reported in the literature (Erbach et al, 1972; Krall et al, 1977; Johnson and Mulvaney, 1980; Muldoon and Daynard, 1981; Liu et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of within‐row plant spacing variability on grain yield is somewhat unclear. Various studies have demonstrated a corn yield reduction associated with spacing variability (Krall et al, 1977; Vanderlip et al, 1988; Nielsen, 2001), whereas other studies indicate that spacing variability commonly observed in many commercial fields will not reduce grain yield if plant population is adequate (Erbach et al, 1972; Edmeades and Daynard, 1979; Muldoon and Daynard, 1981; Daynard and Muldoon, 1983; Liu et al, 2004a, 2004b). In contrast, uneven emergence almost always reduces grain yield, with early emerged plants unable to compensate for lower yield of late‐emerging plants (Carter and Nafziger, 1989; Nafziger et al, 1991; Ford and Hicks, 1992; Liu et al, 2004b).…”
mentioning
confidence: 99%
“…For corn, studies on the effect of within‐row plant uniformity on yield are numerous but results are contradictory. Some studies show significant yield decreases due to nonuniform spacing and plant density (Krall et al, 1977; Nielsen, 2001) while others do not (Erbach et al, 1972; Liu et al, 2004). Reconciling the causes leading to these different conclusions is complicated partly by the dramatic improvements in genetics that support higher plant densities and also the confounding role of different growing environments (Martin et al, 2005).…”
mentioning
confidence: 99%